Canadian SMES in the Tourism Sector: A Taxonomy of Owner-Managers - Ibanescu, Mihai; Chirita, Gabriel; Keen, Christian; Cisneros, Luis (Management international / International Management / Gestiòn Internacional, 2019)
In the tourism sector, owner-managers have distinct characteristics. SMEs face unique challenges for growth. This study explores the characteristics of Canadian owner-managers of tourism SMEs. We conducted a research based on focus groups and questionnaires. We developed a method of classifying these owner-managers considering their propensity to invest and renew their offerings and the evolution of their firms in terms of profits. A two-step multidimensional cluster analysis gives us six categories of owner-managers: Lifestyles, Procrastinators, Harvesters, Gamblers, Strugglers, and Performers. We explain these categories and discuss recommendations.